PENGARUH PROMOSI TERHADAP CITRA PERUSAHAAN PADA HOTEL RESTY MENARA PEKANBARU - Emmy Oktavianty Tampubolon; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Resty Menara Hotel is one of the 3 star hotel (***) in Pekanbaru and located Jl. Sisimangaraja no. 89 Pekanbaru. Resty Menara Hotel Pekanbaru do promotions make up one of the marketing mix. Implementation of the promotion is expected to add a positive image on Resty Menara Hotel Pekanbaru. Implementation of promotion at Resty Menara Hotel Pekanbaru are advertising, personal selling, sales promotion, public reation.In this research methodology used is descriptive and quantitative with SPSS, where the sample used is Resty Menara Hotel Pekanbaru and as a source of information is the Marketing Manager. To determine the sample using slovin test, sampling with accidental sampling method. Data collection through interviews and questionnaires.The analysis is a statistical analysis with SPSS version 20. The result of the calculation is the determination coefficient of 0.869. This means that the promotion of a positive significant effect on the image of the company amounted to 86.9%.Keywords: Promotion, Corporate Image, Advertaising